PERANCANGAN SISTEM INFORMASI GEOGRAFIS DESTINASI WISATA PROVINSI JAMBI BERBASIS WEB: Geographic ,Information System, Tourism Destination, Leaflet JS, Laravel, WebGIS - Elzas, Elzas; Mulyati, Sri; Putri Angga Sari, Anisa (LP2M Universitas Nurdin Hamzah, 2025)
This research aims to design and develop a Geographic Information System (GIS) for Mapping Tourist Destinations in Jambi Province at the Department of Culture and Tourism of Jambi Province. The system was developed to overcome the limitations of tourism promotion media, which previously relied only on social media, resulting in less structured information. The research applied the waterfall method, including requirements analysis, system design, implementation, and testing. The system was built using the Laravel framework, MySQL database, and Leaflet JS library with OpenStreetMap as the base map. The results show that the system can present tourist destination information in an interactive digital map, complete with location details, descriptions, facilities, galleries, accommodations, and tour guides. This system enables the public to access tourism information more easily and provides the department with a more effective tool for managing and promoting tourism.